Modelling primaquine-induced haemolysis in G6PD deficiency - White, N; Watson, J; Taylor, R; Menard, D; Kheng, S (eLife Sciences Publications, 2017)
Primaquine is the only drug available to prevent relapse in vivax malaria. The main adverse effect of primaquine is erythrocyte age and dose dependent acute haemolytic anaemia in individuals with glucose-6-phosphate dehydrogenase deficiency (G6PDd). As testing for G6PDd is often unavailable this limits the use of primaquine for radical cure. A compartmental model of the dynamics of red blood cell production and destruction was designed to characterise primaquine-induced haemolysis using a holistic Bayesian analysis of all published data and was used to predict a safer alternative to the currently recommended once weekly 0.75mg/kg regimen for G6PDd. The model suggests that a step-wise increase in daily administered primaquine dose would be relatively safe in G6PDd. If this is confirmed then were this regimen to be recommended for radical cure patients would not require testing for G6PDd in areas where G6PD Viangchan or milder variants are prevalent.